Identification of Target Sites of the α2–Mcm1 Repressor Complex in the Yeast Genome - Zhong, Hualin; McCord, Ron; Vershon, Andrew K.

(untitled) (Genome Research, 1999)
The α2 and Mcm1 proteins bind DNA as a heterotetramer to repress transcription of cell-type-specific genes in the yeastSaccharomyces cerevisiae. Based on the DNA sequence requirements for binding by the α2–Mcm1 complex, we have searched the yeast genome for all potential α2–Mcm1 binding sites. Genes adjacent to the sites were examined for expression in the different cell mating types. These sites were further analyzed by cloning the sequences into a heterologous promoter and assaying for α2–Mcm1-dependent repression in vivo and DNA-binding affinity in vitro. Fifty-nine potential binding sites were identified in the search. Thirty-seven sites are located within or downstream of coding region of the gene. None of the sites assayed from this group are functional repressor sites in vivo or bound by the α2–Mcm1 complex in vitro. Among the remaining 22 sites, six are in the promoters of known α-specific genes and two other sites have an α2–Mcm1-dependent role in determining the direction of mating type switching. Among the remaining sequences, we have identified a functional site located in the promoter region of a previously uncharacterized gene, SCYJL170C. This site functions to repress transcription of a heterologous promoter and the α2–Mcm1 complex binds to the site in vitro. SCYJL170C is repressed by α2–Mcm1 in vivo and therefore using this method we have identified a new a-specific gene, which we callASG7.